1996
DOI: 10.1063/1.115702
|View full text |Cite
|
Sign up to set email alerts
|

Degenerate-four-wave-mixing of fullerene doped inorganic glass

Abstract: A very recently developed high Tm (melting temperature) optical glass doped with C60/C70 molecules has been studied. Using a picosecond laser operating at 532 nm, the observed time-resolved degenerate-four-wave-mixing (DFWM) spectra show remarkable changes with addition of fullerene into the glass host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The values of the thirdorder nonlinear optical susceptibility (χ (3) ) and molecular second hyperpolarizability (γ) were 9.7 × 10 -11 and 9.6 × 10 -32 esu, respectively. A comparison of the γ values reported in the literature for pristine and chemically modified C 60 in solutions [11][12][13][14] and solid-state [15][16][17] with the value reported herein 18 is shown in Figure 3. We show for reference the calculated physical limits for these molecular systems.…”
mentioning
confidence: 81%
“…The values of the thirdorder nonlinear optical susceptibility (χ (3) ) and molecular second hyperpolarizability (γ) were 9.7 × 10 -11 and 9.6 × 10 -32 esu, respectively. A comparison of the γ values reported in the literature for pristine and chemically modified C 60 in solutions [11][12][13][14] and solid-state [15][16][17] with the value reported herein 18 is shown in Figure 3. We show for reference the calculated physical limits for these molecular systems.…”
mentioning
confidence: 81%
“…Together with photophysical properties, the third order nonlinear optical susceptibility of fullerenes has been measured by degenerate four-wave mixing (DFWM) experiments in PMMA films doped with C 60 and C 70 mixture (80% C 60 and 20% C 70 ) 16 and in phosphate glasses doped with C 60 /C 70 . 17,18 The third harmonic generation technique 19 has been used with sol-gel hybrid samples doped with a fullerene derivative. All these experiments demonstrated that both fullerenes and fullerene derivatives show good NLO responses.…”
Section: Fullerenes: Linear and Nonlinear Optical Properties And Opti...mentioning
confidence: 99%
“…These molecules have a large number of conjugated double bonds providing extensive π-electron delocalization, which may lead to large nonlinear polarizabilities . As a result, considerable attention has been directed toward the nonlinear optical properties of these molecules, and numerous investigations on different aspects of the nonlinearity have been carried out. Due to the centrosymmetric structure of C 60 , the second-order polarizability is zero, while the third-order optical polarizability is always symmetry allowed. Then, the greatest nonlinearity in these molecules should arise from the third-order susceptibility tensor χ (3) , which is the quantity that has attracted the interest of experimentalists.…”
Section: Introductionmentioning
confidence: 99%
“…In some of the previous studies on the third-order optical nonlinearity of C 60 in different media, ,,,,, evidence was presented of the existence of two components in the nonlinearity, one of them with a response on the picosecond time scale and the other with a decay time much longer than picoseconds. It was suggested 7,8,18,25 that the slow component could originate from a thermal grating created by the nonuniform heating of the medium by the interacting beams, but no further investigation was carried out on this component, and only Vijaya et al.…”
Section: Introductionmentioning
confidence: 99%